PENERAPAN MEDIA FLASHCARD DIGITAL BERBASIS CANVA UNTUK MENINGKATKAN PEMAHAMAN BACAAN KOSAKATA BAKU SISWA KELAS IV SEKOLAH DASAR - Fatia Zulfa Nurhafifah; Assalwa Tazkiya. L; Ihsan Syah Putra; Risdalina, Risdalina; Destrinelli, Destrinelli (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was conducted with the aim of improving reading comprehension of standard vocabulary among fourth-grade students at SDN 080/I KM 3 Ma. Bulian through the implementation of an innovative learning medium in the form of digital flashcards created using Canva. The research employed a Classroom Action Research (CAR) method carried out in two cycles, each consisting of planning, action, observation, and reflection stages. The results showed that the use of digital flashcard media increased the students’ average score from 68 in the first cycle to 82 in the second cycle and also increased the number of students who scored above average. This improvement indicates that Canva-based interactive visual media is effective in capturing students' attention, encouraging active participation in learning, and enhancing understanding of standard vocabulary within reading contexts. These findings are expected to serve as a reference for teachers in developing instructional media that align with the characteristics and needs of elementary school students in the digital era.